2014
DOI: 10.1186/1472-6882-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Genistein inhibits tumor invasion by suppressing multiple signal transduction pathways in human hepatocellular carcinoma cells

Abstract: BackgroundGenistein (Gen) exhibits anti-mutagenic and anti-metastatic activities in hepatoma cell lines. Gen has suppressive effects on tumor growth and angiogenesis in nude mice. Gen suppresses the enzymatic activity of matrix metalloproteinase (MMP)-9; however, the mechanism underlying its anti-invasive activity on hepatocellular carcinoma (HCC) cells is unclear.MethodsIn this study, the possible mechanisms underlying Gen-mediated reduction of 12-O-Tetradecanoylphorbol-13-acetate (TPA)-induced cell invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Our study revealed that genistein and daidzein increased the ovarian follicular reserve in middle-aged rats by stepping down the transition from primordial to primary follicle and by depressing follicular atresia. The mechanisms may be explained by the suppression of cellular proliferation through the inhibition of key steps in the signal transduction pathways [46] and cell cycle progression [47,48], indicating that genistein and daidzein may play a role in suppressing the process of follicular development by scavenging and suppressing intracellular reactive oxygen intermediates. Therefore, we presume that phytoestrogens may protect follicles from atresia due to the decrease of oxidative stress in the ovary.…”
Section: Discussionmentioning
confidence: 98%
“…Our study revealed that genistein and daidzein increased the ovarian follicular reserve in middle-aged rats by stepping down the transition from primordial to primary follicle and by depressing follicular atresia. The mechanisms may be explained by the suppression of cellular proliferation through the inhibition of key steps in the signal transduction pathways [46] and cell cycle progression [47,48], indicating that genistein and daidzein may play a role in suppressing the process of follicular development by scavenging and suppressing intracellular reactive oxygen intermediates. Therefore, we presume that phytoestrogens may protect follicles from atresia due to the decrease of oxidative stress in the ovary.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, genistein has been shown to inhibit the migration of 3 cell lines (HepG2, SMMC-7721, and Bel-7402 cells) (109). Moreover, it promotes anti-invasive and antimetastatic effects against 12-O-tetradecanoylphorbol-13-acetate-mediated metastasis via downregulation of matrix metalloproteinase 9 (MMP-9) and epidermal growth factor receptor (EGFR) and subsequent suppression of NF-kB and activator protein 1 (AP-1) transcription factors through inhibition of MAPK, inhibitor of NF-kB (IkB), and phosphoinositide 3 kinase/Akt (PI3K/Akt) signaling pathways (110).…”
Section: Genistein and Cancermentioning
confidence: 99%
“…Thus, inhibition of NF-κB activity in cancer/endothelial cells may provide a target for cancer treatment and/or prevention. Recently, Wang et al [109] have found that genistein suppressed MMP-9 transcription by inhibiting NF-κB activity. It suppressed 12- O -tetradecanoylphorbol-13-acetate (TPA)-induced NF-κB—specific DNA-protein binding compared to TPA via inhibition of NF-κB nuclear translocation through inhibitor of kappa B inhibitory signaling pathways.…”
Section: Antiangiogenic Effect Of Soy Isoflavonoidsmentioning
confidence: 99%